PENGGUNAAN LABA, ARUS KAS DAN LEVERAGE UNTUK MEMPREDIKSI KONDISI KEUANGAN FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR TRASPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2021 (STUDI KASUS PT GARUDA INDONESIA) - Sadili, Sherly Marcella; Maharani, Yunita; Medinal (Jurnal Ilmiah Niaga Bisnis Elektronik, 2023)
The purpose of this study was to determine the effect of cash flow and earnings on financial distress. Data was obtained form secondary data, which was obtained from parties in the form of publication reports for the 2015-2021 period (case study of PT Garuda Indonesia). The financial distress measurement method uses the Altman z-score method. The results of the study show (1) Profit has no significant effect on predicting financial distress. (2) Cash flow has no effect on predicting financial distress conditions. (3) Leverage has no effect on predicting financial distress conditions. And simultaneously this study states that profit, cash flow and leverage have no effect on predicting financial distress.